2012
DOI: 10.5414/te0x1238
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of trace elements nutritional habits in patients with HCV with or without interferon therapy

Abstract: Aim: The most common treatment of HCV is a therapy with interferon a (INF-a), which could escalate appetite problems in patients. The anorexia and liver damage force suffers to adhere to a special diet, which can reduce the negative effects among the participants' interferon therapy. Thus, the aim of this preliminary study was to assess the trace elements nutritional habits in patients with HCV with and without the interferon therapy. Method: The study was carried out in 50 patients with HCV, males (n = 24) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…The scientific evidence on this topic is rather inadequate. Previous studies by this author on the distribution of micronutrients in different populations exposed to a reduction in food and energy intake (such as cystic fibrosis patients, hepatitis C virus infected patients treated with interferon, obese children on special low calorie diets, and women with vegetarian diets) have shown significantly lower levels of selected trace elements in hair, serum, and urine compared to the normal or reference values [ 3 , 4 , 23 , 24 ]. These observations suggest that in people using free-will starvation as a method of weight loss, similar deficiencies might be observed.…”
Section: Discussionmentioning
confidence: 99%
“…The scientific evidence on this topic is rather inadequate. Previous studies by this author on the distribution of micronutrients in different populations exposed to a reduction in food and energy intake (such as cystic fibrosis patients, hepatitis C virus infected patients treated with interferon, obese children on special low calorie diets, and women with vegetarian diets) have shown significantly lower levels of selected trace elements in hair, serum, and urine compared to the normal or reference values [ 3 , 4 , 23 , 24 ]. These observations suggest that in people using free-will starvation as a method of weight loss, similar deficiencies might be observed.…”
Section: Discussionmentioning
confidence: 99%
“…), are 3 times more likely to suffer from iron deficiency than those women with normal diets [ 1 , 4 6 ]. In previous research the low tissue iron as a result of low iron intake was often observed [ 4 8 ]. Women are at risk of iron deficiency not only because of insufficient intake of this metal, but also the greatest risk of iron deficiency anemia occurs through the combined effects of suboptimal iron consumption and menstrual bleeding, which negatively influences iron balance.…”
Section: Introductionmentioning
confidence: 99%